Crystal Structure and Thermodynamic Stability of Ba/Ti‐Substituted Pollucites for Radioactive Cs/Ba Immobilization. Issue 8 (23rd April 2015) - Xu, Hongwu; Chavez, Manuel E.; Mitchell, Jeremy N.; Garino, Terry J.; Schwarz, Haiqing L.; Rodriguez, Mark A.; Rademacher, David X.; Nenoff, Tina M.; Vance, L.
<x xml:space="preserve">Abstract</x> As an analogue of the mineral pollucite (CsAlSi2O6), CsTiSi2O6.5 is a potential host phase for radioactive Cs. However, as 137Cs and 135Cs transmute to 137Ba and 135Ba, respectively, through the beta decay, it is essential to study the structure and stability of this phase upon Cs → Ba substitution. In this work, two series of Ba/Ti‐substituted samples, CsxBa(1−x)/2TiSi2O6.5 and CsxBa1−xTiSi2O7−0.5x, (x = 0.9 and 0.7), were synthesized by high‐temperature crystallization from their respective precursors. Synchrotron X‐ray diffraction and Rietveld analysis reveal that while CsxBa(1−x)/2TiSi2O6.5 samples are phase‐pure, CsxBa1−xTiSi2O7−0.5x samples contain Cs3x/(2+x)Ba(1−x)/(2+x)TiSi2O6.5 pollucites (i.e., also two‐Cs‐to‐one‐Ba substitution) and a secondary phase, fresnoite (Ba2TiSi2O8). Thus, the CsxBa1−xTiSi2O7−0.5x series is energetically less favorable than CsxBa(1−x)/2TiSi2O6.5. To study the stability systematics of CsxBa(1−x)/2TiSi2O6.5 pollucites, high‐temperature calorimetric experiments were performed at 973 K with or without the lead borate solvent. Enthalpies of formation from the constituent oxides (and elements) have thus been derived. The results show that with increasing Ba/(Cs + Ba) ratio, the thermodynamic stability of these phases decreases with respect to their component oxides. Hence, from the energetic viewpoint, continued Cs → Ba transmutation tends to destabilize the parent silicotitanate pollucite structure. However, the Ba‐substituted pollucite co‐forms with fresnoite (which incorporates the excess Ba), thereby providing viable ceramic waste forms for all the Ba decay products.